Theoretical study on the mechanism of the reaction of FOX-7 with OH and NO2 radicals: bimolecular reactions with low barrier during the decomposition of FOX-7. (2nd December 2017) - Zhang, Ji-Dong; Zhang, Li-Li
ABSTRACT: The decomposition of 1, 1-diamino-2, 2-dinitroethene (FOX-7) attracts great interests, while the studies on bimolecular reactions during the decomposition of FOX-7 are scarce. This study for the first time investigated the bimolecular reactions of OH and NO2 radicals, which are pyrolysis products of ammonium perchlorate (an efficient oxidant usually used in solid propellant), with FOX-7 by computational chemistry methods. The molecular geometries and energies were calculated using the (U)B3LYP/6-31++G(d, p) method. The rate constants of the reactions were calculated by canonical variational transition state theory. We found three mechanisms (H-abstraction, OH addition to C and N atom) for the reaction of OH + FOX-7 and two mechanisms (O abstraction and H abstraction) for the reaction of NO2 + FOX-7. OH radical can abstract H atom or add to C atom of FOX-7 with barriers near to zero, which means OH radical can effectively degrade FOX-7. The O abstraction channel of the reaction of NO2 + FOX-7 results in the formation of NO3 radical, which has never been detected experimentally during the decomposition of FOX-7. Abstract :